EFFECTIVENESS OF DIGITAL MARKETING: AS A NEW STRATEGY TOOL FOR VALUE OF CUSTOMER’S SERVICES PERSPECTIVE IN LIBYAN TELECOMMUNICATION INDUSTRY - Omran Elgahwash, Fouad (International Journal of Psychosocial Rehabilitation, 2021)
Digital marketing theories, practices, and models from other industries are adopted anapplied to the local communication industry to lay the foundation for making it smart andsustainable. Digital Marketing is growth of online shopping and increase in technologicalchanges business’ future.This paper focuses on Libyan Telecommunications companies-based, in technology changes.The greatest key in today’s technologies is to achieve a balance on both offline and onlinestores and services, which is possible through customer loyalty and value in the digitalizationera. It is not only providing useful insights as customer views and also possible areas ofresearch which could have further value addition in terms of growing in this industry. Adescriptive approach is adopted, using an online questionnaire tool to investigate thebehavior of respondents on the current digital marketing practices and capabilities of LibyanTelecommunication companies.Today, many Libyan telecom companies attempt to take advantage of digital marketingchannels to provide suitable services for customers anywhere to improve their satisfactionlevel. The population consisted of experts in communications industry to identify mostimportant of digital marketing.In particular, in the era of digital marketing, customers have more media channels to choosefrom and traditional marketing models affected heavily by Internet- smartphones and socialmedia-based marketing for developing new customer groups or new market segments.